Multifunctional cytomegalovirus (CMV)‐specific CD8+ T cells are not restricted by telomere‐related senescence in young or old adults. Issue 4 (April 2015) - Riddell, Natalie E.; Griffiths, Stephen J.; Rivino, Laura; King, David C. B.; Teo, Guo H.; Henson, Sian M.; Cantisan, Sara; Solana, Rafael; Kemeny, David M.; MacAry, Paul A.; Larbi, Anis; Akbar, Arne N.
Summary Antigen‐specific multifunctional T cells that secrete interferon‐γ, interleukin‐2 and tumour necrosis factor‐α simultaneously after activation are important for the control of many infections. It is unclear if these CD8+ T cells are at an early or late stage of differentiation and whether telomere erosion restricts their replicative capacity. We developed a multi‐parameter flow cytometric method for investigating the relationship between differentiation (CD45RA and CD27 surface phenotype), function (cytokine production) and replicative capacity (telomere length) in individual cytomegalovirus (CMV) antigen‐specific CD8+ T cells. This involves surface and intracellular cell staining coupled to fluorescence in situ hybridization to detect telomeres (flow‐FISH). The end‐stage/senescent CD8+ CD45RA+ CD27− T‐cell subset increases significantly during ageing and this is exaggerated in CMV immune‐responsive subjects. However, these end‐stage cells do not have the shortest telomeres, implicating additional non‐telomere‐related mechanisms in inducing their senescence. The telomere lengths in total and CMV (NLV)‐specific CD8+ T cells in all four subsets defined by CD45RA and CD27 expression were significantly shorter in old compared with young individuals in both a Caucasian and an Asian cohort. Following stimulation by anti‐CD3 or NLV peptide, similar proportions of triple‐cytokine‐producing cells are found in CD8+ T cells at all stages of differentiation in both age groups. Furthermore, these multi‐functional cells had intermediate telomere lengths compared with cells producing only one or two cytokines after activation. Therefore, global and CMV (NLV)‐specific CD8+ T cells that secrete interferon‐γ, interleukin‐2 and tumour necrosis factor‐α are at an intermediate stage of differentiation and are not restricted by excessive telomere erosion.